THE INFLUENCE OF KNOWLEDGE MANAGEMENT, LEADER MEMBER EXCHANGE AND JOB EMBEDDEDNESS ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR: AN EMPIRICAL STUDY ON INDONESIAN PUBLIC SECTOR GOVERNANCE EMPLOYEE - Yusuf, Muhamad (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
This study aims to analyze the effect of Leader Member Exchange and job embeddedness on Organizational Citizenship Behavior of Public Sector Governance Employees. This type of research is an associative and guantitative type. The population in this study are all Public Sector Governance Employees with a total of 670 employees. The sampling method in this study uses a non-probability method sampling with a total sample of 232 employees determined by the simple random sampling method. Data collection technigues used online guestionnaires, while data analysis technigues in this study used structural eguation modeling (SEM) analysis. The results of this study indicate that partially, Leader member exchange has a positive and significant effect on Organizational Citizenship Behavior Public Sector Governance Employee Partially, Job Embeddedness has a positive and significant effect on Organizational Citizenship Behavior on Public Sector Governance Employee, knowledge management has a positive and significant effect Organizational Citizenship Behavior.